Ivermectin use in children below 15 kg: potential benefits for onchocerciasis and scabies elimination programmes. (1st April 2020) - Colebunders, R.; Wafula, S.T.; Hotterbeekx, A.; Siewe‐Fodjo, J. N.
Abstract: Linked Article: Levy et al. Br J Dermatol 2020; 182 :1003–6 .